Targeted and non-targeted analysis for the investigation of pesticides influence on wheat cultivated under field conditions. (1st January 2023) - Pszczolińska, Klaudia; Perkons, Ingus; Bartkevics, Vadims; Drzewiecki, Sławomir; Płonka, Joanna; Shakeel, Nasir; Barchanska, Hanna
Abstract: A comprehensive approach was applied to evaluate the effects of pesticides on the metabolism of wheat ( Triticum aestivum L). The application of commercially available pesticide formulations under field cultivation conditions provided a source of metabolic data unlimited by model conditions, representing a novel approach to study the effects of pesticides on edible plants. Gas and liquid chromatography coupled to tandem mass spectrometry were employed for targeted and non-targeted analysis of wheat roots and shoots sampled six times during the six-week experiment. The applied pesticides: prothioconazole, tebuconazole, fluoxastrobin, diflufenican, florasulam, and penoxulam were found at concentrations ranging 0.0070–25.20 mg/kg and 0.0020–2.2 mg/kg in the wheat roots and shoots, respectively. The following pesticide metabolites were identified in shoots: prothioconazole-desthio (prothioconazole metabolite), 5-(4-chlorophenyl)-2, 2-dimethyl-3-(1, 2, 4-triazol-1-ylmethyl)pentane-1, 3-diol (tebuconazole metabolite), and N -(5, 8-dimethoxy[1, 2, 4]triazolo[1, 5-c]pyrimidin-2-yl)-2, 4-dihydroxy-6-(trifluoromethyl)benzene sulphonamide (penoxulam metabolite). The metabolic fingerprints and profiles changed during the experiment, reflecting the cumulative response of wheat to both its growth environment and pesticides, as well as their metabolites. Approximately 15 days after the herbicide treatment no further changes in the plant metabolic profiles were observed, despite the presence of pesticide and their metabolites in both roots and shoots. This is the first study to combine the determination of pesticides and their metabolites plant tissues with the evaluation of plant metabolic responses under field conditions. This exhaustive approach contributes to broadening the knowledge of pesticide effects on edible plants, relevant to food safety. Graphical abstract: Image 1 Highlights: Herbicides and fungicides metabolism in plants was investigated under field conditions Pesticide disappearance kinetics were determined in wheat roots and shoots The metabolites of herbicides and fungicides in shoots were identified Pesticide and their metabolites influence wheat metabolic fingerprint